Development and characterization of dense membranes for gas separation made from high molecular weight sulfonated poly (phenylene oxide): Effect of casting conditions on the morphology and performance of the membranes. - Kruczek, Boguslaw. (University of Ottawa (Canada), 1999)
Membrane gas separation emerged as an alternative gas separation technology 20 years ago. In comparison with traditional gas separation technologies, membranes offer a number of advantages, including low capital and operational costs along with simplicity and flexibility of operation. On the other hand, membranes cannot compete on the basis of product purity. Improvements in this area require development and characterization of new membrane materials with better gas separation properties compared to the existing polymers. This research was focused on the improvement of gas transport properties of poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) by chemical and physical modifications of the polymer. The study was divided into two parts: (1) chemical modifications of PPO along with characterization of the products; (2) investigation of the effect of casting conditions. High molecular weight PPO was sulfonated to different ion exchange capacity (IEC) values with chlorosulfonic acid. The resulting polymer, sulfonated PPO in the acid form (HSPPO), was further modified by substituting the proton in sulfonic groups by various metal cations including Na +, Mg2+, and Al3+. Some physical properties such as density, thermal stability, and x-ray diffraction as well as the gas transport properties of the membranes were determined. Substitution of the proton in sulfonic groups by metal cations increases polarity and density of the polymer. In some instances, a small increase in d-spacing and X-ray diffraction is also observed. Introduction of metal cation into the polymer backbone improves its thermal stability. Despite a greater density, MeSPPO is more permeable to gases compared to the corresponding HSPPO. To investigate the effect of casting conditions dense membranes were prepared using different solvents in casting solution. In addition two series of dense membranes were prepared in which solution temperature and the film casting temperature were controlled separately. The change of solvent in casting solution results in changes of more than two-fold in gas permeability and changes of up to 12% in permeability ratio of the membrane. The changes in gas transport properties are associated with significant changes in the surface morphology of the membrane. This study has also revealed some interesting relationship between the testing system and the obtained gas transport data. In particular, membranes tested in a system in which permeate side is open to atmosphere are influenced by relative humidity in the atmosphere. An increase in relative humidity in the atmosphere increases the apparent CO2 permeability and CO 2/CH4 permeability ratio and decreases the apparent O 2 permeability and O2/N2 permeability ratio. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.